Do individuals with inflammatory arthritis receive minimally adequate treatment for incident depression and anxiety: A population-based study - Alyssa Howren; Eric C. Sayre; J. Antonio Avina-Zubieta; Joseph H. Puyat; Deborah Da Costa; Hui Xie; Eileen Davidson; Amit Gupta; Mary A. De Vera (Arthritis Research & Therapy)
Abstract Objectives Describe patterns of pharmacotherapy and psychological treatment and evaluate receipt of minimally adequate treatment for incident depression and anxiety in individuals with inflammatory arthritis (IA). Methods We used population-based linked administrative health databases from British Columbia, Canada to evaluate pharmacotherapy and psychological treatments for incident depression and/or anxiety among individuals with IA and without IA (‘IA-free controls’). We defined minimally adequate pharmacotherapy as antidepressant prescriptions filled with ≥ 84 days’ supply and adequate psychological treatment as ≥ 4 counselling/psychotherapy services. Multivariable logistic regression models were used to evaluate the odds of individuals with IA receiving minimally adequate pharmacotherapy and/or psychological treatment compared to IA-free controls. Results 6,951 (mean age 54.8 ± 18.3 years; 65.5% female) individuals with IA had incident depression and 3,701 (mean age 52.9 ± 16.8 years; 74.3% female) had incident anxiety. Minimally adequate pharmacotherapy and psychological treatment for depression was respectively observed in 50.5% and 19.6% of those with IA, proportions similar to IA-free controls (pharmacotherapy: aOR 1.10, 95% CI 1.00 to 1.21; psychological: aOR 1.07, 95% CI 0.94 to 1.21). Results were similar regarding anxiety treatment. Individuals with IA had a significantly greater likelihood of dispensing ≥ 1 benzodiazepine (anxiety: IA 45.0%, IA-free controls 39.0%, p-value < 0.001) and ≥ 1 tricyclic antidepressant prescription (anxiety: IA 12.8%, IA-free controls 7.8%, p-value < 0.001). Significantly higher average days’ supply of benzodiazepines was observed for IA (anxiety: IA 123.7 days, controls 112.4 days, p-value = 0.003). Conclusions A substantial proportion of individuals with IA were not receiving adequate mental health treatment for depression and anxiety, a finding similar for IA-free controls. The undertreatment of mental disorders for people with IA has well-known negative implications for the provision of effective rheumatology care. It remains fundamental to expand publicly funded health care to include mental health services in an effort to address unmet counselling needs.